Armored Scale Insects (Hemiptera: Diaspididae) on Dypsis lutescens and Phoenix roebelenii (Arecaceae) in Urban Environments of Costa Rica - Solano-Gutiérrez, Minor V.; Hanson, Paul (Entomological Communications, 2025)
Armored scales (Hemiptera: Diaspididae) were collected from Dypsis lutescens (H. Wendl) Beentje & J. Dransf., 1995, and Phoenix roebelenii O’Brien, 1889, in urban Costa Rica. Lopholeucaspis cockerelli (Grandpré & Charmoy, 1899), previously known only from intercepted plant material, was found on both palms (P. roebelenii—new host record). Pseudischnaspis bowreyi (Cockerell, 1893), also previously recorded only from interceptions, was identified on both species (new host records). Ischnaspis longirostris (Signoret, 1882) was identified on both palms, Selenaspidus articulatus (Morgan, 1889) on P. roebelenii (new host record), Hemiberlesia cyanophylli Signoret, 1869 on P. roebelenii (new host record) and D. lutescens, H. palmae (Cockerell, 1893) on P. roebelenii (new host record) and D. lutescens, Pinnaspis strachani (Cooley, 1899) on D. lutescens, Pinnaspis apidistrae (Signoret, 1869) on D. lutescens and P. roebelenii (new host record), Diaspis boisduvalii Signoret, 1869 on P. roebelenii, Chrysomphalus dictyospermi (Morgan, 1889) on both palms (new host records), Lepidosaphes gloverii (Packard, 1869) on P. roebelenii (new host record), and Aspidiotus destructor Signoret, 1869 on both palms. Among parasitoids, Aphytis sp. (Hymenoptera: Aphelinidae) was reared from C. dictyospermi and I. longirostris, and Signiphora sp. (Hymenoptera: Signiphoridae) from H. cyanophylli and I. longirostris. This is the first record of a species of Signiphora Ashmead, 1880 parasitizing I. longirostris. The identified armored scales are highly polyphagous and not exclusive to palms, highlighting the need for further research on their diversity and ecology, as well as their natural enemies, in tropical urban environments.